Trait anxiety and its relationship to scoring accuracy in five-a-side football among students of the College of Physical Education and Sports Sciences, University of Maysan (Texas Journal of Multidisciplinary Studies, 2024)
The research study aimed to identify the relationship between trait anxiety and scoring accuracy in futsal among students of the College of Physical Education and Sports Sciences, University of Maysan. The researcher assumed the existence of a statistically significant relationship between trait anxiety and scoring accuracy in futsal. The researcher used the descriptive approach using the survey method as it is the best and easiest method in achieving the research objectives, as survey studies focus on the present and study the situation in greater depth, while providing the researcher with detailed and analytical information called the study of the current situation. The research sample included (26) students out of (30) students after excluding (4) students for lack of cooperation, where the sample percentage was (40)% of the total original community. The research results showed the emergence of a statistically significant correlation between trait anxiety and scoring accuracy in futsal.